Immigrant wage and employment assimilation: A comparison of methods - Deborah A. Cobb-Clark; Barbara Hanel; Duncan McVicar (Institute for the Study of Labor (IZA), 2012)
We compare alternative methods for estimating immigrant wage and employment assimilation using unique panel data over 2001-2009 for a large, nationally-representative sample of immigrants. Previous assimilation estimates have been mainly based on cross-sectional data and have therefore suffered from a range of potential biases. We find that a fixed-effects model generates estimated employment assimilation profiles that are flatter and significantly different to those produced by cross-sectional and synthetic cohort methods. However, there are no significant differences in the wage assimilation profiles across alternative methods.
Keywords: J15; J61; 330; immigration; immigrant assimilation; employment; wages; Australia; Lohndifferenzierung; Migranten; Berufliche Integration; Australien